Perancangan Program Aplikasi Data Produk Pada PT.KDS INDONESIA Menggunakan PHP Dan MySQl - Angger Bagas Willian Prakoso (ALMUISY: Journal of Al Muslim Information System, 2023)
An efficient, fast, accurate and safe inventory of goods is needed for a part in the company. The production data application will support the work of foreman and leader to collect data on stocqk of goods in a production department and make reports efficiently and quickly, and do not require double work to process it. The production data application at PT. KDS INDONESIA is designed with several stages, data and information collection, needs analysis and application design, application development and application testing. This application was developed using PHP and MySQL. This application provides facilities that can be used by foreman in the form of input data, incoming goods, outgoing goods, location of goods and operator data. Keywords: Application Development, Production Goods Stock Data